2012
DOI: 10.1051/0004-6361/201219093
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the neutron star spin and a possible orbital period from the Be/X-ray binary IGR J05414-6858 in the LMC

Abstract: Context. The number of known Be/X-ray binaries in the Large Magellanic Cloud is small compared to the observed population of the Galaxy or the Small Magellanic Cloud. The discovery of a system in outburst provides the rare opportunity to measure its X-ray properties in detail. Aims. IGR J05414-6858 was discovered in 2010 with INTEGRAL and was found in another outburst with the Swift satellite in 2011.To characterise the system, we analysed the data from a follow-up XMM-Newton target of opportunity observation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…As done in our previous papers, we give an update of the statistics concerning the identifications of new hard X-ray INTEGRAL sources including the results of this work and those in Lutovinov et al (2012), Smith et al (2012), Sturm et al (2012), and Ratti et al (2013). Up to now, 240 INTEGRAL objects have been identified through optical or NIR spectroscopy; their separation into the main classes reported in Papers VI-IX is the following: 147 (61.2%) are AGNs, 60 (25.0%) are X-ray binaries, 29 (12.1%) are CVs, and 4 cases (1.7%) are likely identified as active stars.…”
Section: Statisticsmentioning
confidence: 94%
See 2 more Smart Citations
“…As done in our previous papers, we give an update of the statistics concerning the identifications of new hard X-ray INTEGRAL sources including the results of this work and those in Lutovinov et al (2012), Smith et al (2012), Sturm et al (2012), and Ratti et al (2013). Up to now, 240 INTEGRAL objects have been identified through optical or NIR spectroscopy; their separation into the main classes reported in Papers VI-IX is the following: 147 (61.2%) are AGNs, 60 (25.0%) are X-ray binaries, 29 (12.1%) are CVs, and 4 cases (1.7%) are likely identified as active stars.…”
Section: Statisticsmentioning
confidence: 94%
“…Among them, we selected unidentified or unclassified hard X-ray sources containing a single bright soft X-ray object within the IBIS 90% confidence level error box. The latter information was obtained from either the ROSAT all-sky bright source catalogue (Voges et al 1999), Swift/XRT pointings (from Krivonos et al 2009;Rodriguez et al 2009;Maiorano et al 2010;Sturm et al 2011;Kennea 2011;Landi et al 2012a;Luna et al 2012;Molina et al 2012a;Parisi et al 2012, and from the XRT archive 3 ), or Chandra observations (Kaur et al 2010;Tomsick et al 2008). As stressed and demonstrated (see Stephen et al 2006 and Papers I-IX), this procedure is extremely effective in substantially reducing the search area and in pinpointing a putative optical counterpart within the corresponding (sub)arcsecond-sized soft X-ray error box.…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…2010). Using data of the XMM-Newton observations of this source carried out during its outburst in 2011, Sturm et al (2012) revealed X-ray pulsations with a period of ∼ 4.4 s in its light Table 2. Fluxes in the 20-60 keV energy band from the known hard X-ray sources in the LMC field not included in Table 1 curve and classified the source as a X-ray pulsar in a highmass X-ray binary system.…”
Section: High-mass X-ray Binariesmentioning
confidence: 99%
“…About 45 candidates have also been identified during the XMM-Newton survey of the SMC (Sturm et al 2013). While the LMC is about ten times as massive as the SMC, it contains only A&A 554, A1 (2013) 14 confirmed BeXRBs so far (Liu et al 2005;Masetti et al 2006;Sturm et al 2012;Klus et al 2013). This discrepancy is possibly explained by different star formation histories (SFHs).…”
Section: Introductionmentioning
confidence: 99%